Models for transition clinics. (August 2014) - Carrizosa, Jaime; An, Isabelle; Appleton, Richard; Camfield, Peter; Von Moers, Arpad
Summary: Transition is a purposeful, planned process that addresses the medical, psychosocial, educational, and vocational needs of adolescents and young adults with chronic medical conditions, as they advance from a pediatric and family‐centered to an adult, individual focused health care provider. This article describes some of the models for transition clinics or services for epilepsy in five countries (Canada, France, Colombia, Germany, and the United Kingdom). These models include joint adult and pediatric clinics, algorithm‐driven service, and a check list system in the context of pediatric care. Evaluation of these models is limited, and it is not possible to choose an optimal program. The attitude and motivation of health care providers may be the most important elements.